Effect of light and dark on callus induction and regeneration in tobacco (Nicotiana tabacum L.) - Siddique, Abu Baker; Islam, SM Shahinul (Bangladesh Journal of Botany, 2018)
To determine the effect of light and dark on callus induction and plant regeneration from five different explants of three tobacco varieties were studied. Normal white light (3000 lux) and dark conditions were considered for callus induction. Among the explants earliest callusing initiated at 5th day from nodal segment and the highest amount of callus (97.20%) was recorded from leaf blade of Motihari variety in light condition. The lowest callusing was recorded 24.40% in dark condition for root of Virginia variety and it was initiated after 13 days of culture initiation. The calli developed in dark showed watery, glossy silver color and less embryogenic features. The highest plant regeneration (95.56%) was recorded from nodal segment in light which was around five times higher than root in dark for Motihari variety. Nodal segments that received light (treatment) showed maximum relative growth rate (4.58) for Motihari variety while the lowest value was 0.91 scored from root of Virginia variety which received dark treatment.